Social Allostasis: Anticipatory Regulation of the Internal Milieu - Schulkin, Jay (Frontiers in Evolutionary Neuroscience, 2011)
Social regulation of the internal milieu is a fundamental behavioral adaptation. Cephalic capability is reflected by anticipatory behaviors to serve systemic physiological regulation. Homeostatic regulation, a dominant perspective, reflects reactive responses; allostatic regulation, the physiology of change, emphasizes longer-term anticipatory, and feedforward systems. Steroids, such as cortisol, and peptides such as corticotrophin releasing hormone are but one example of such anticipatory regulatory systems. The concept of “allostasis” is in part to take account of anticipatory control amidst diverse forms of adaptation underlying this regulatory adaptation that supports social contact and internal milieu.